2017
DOI: 10.4038/cjs.v46i2.7425
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater fluoride as a geochemical marker in the etiology of chronic kidney disease of unknown origin in Sri Lanka

Abstract: Abstract:The correlation of chronic kidney diseases of unknown etiology (CKDu)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 29 publications
3
47
0
Order By: Relevance
“…The present findings are crucial to a recent report that highlighted groundwater F as a geological marker in the aetiology of chronic kidney diseases of unknown aetiology (CKDu) in Sri Lanka. It is caused by a complex biochemical interaction among Ca, Mg, Na and F ions in the groundwater . Meanwhile, the F level in water consumed by CKDu patients in Sri Lanka varies from 0.05 to 4.8 mg/L, with the mean value of 0.78 mg/L .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present findings are crucial to a recent report that highlighted groundwater F as a geological marker in the aetiology of chronic kidney diseases of unknown aetiology (CKDu) in Sri Lanka. It is caused by a complex biochemical interaction among Ca, Mg, Na and F ions in the groundwater . Meanwhile, the F level in water consumed by CKDu patients in Sri Lanka varies from 0.05 to 4.8 mg/L, with the mean value of 0.78 mg/L .…”
Section: Discussionmentioning
confidence: 99%
“…It is caused by a complex biochemical interaction among Ca, Mg, Na and F ions in the groundwater. 28 Meanwhile, the F level in water consumed by CKDu patients in Sri Lanka varies from 0.05 to 4.8 mg/L, with the mean value of 0.78 mg/L. 29 Hence, the country should have a plan to maintain an optimal level of F in groundwater as an approach to mitigate both dental fluorosis and CKDu in Sri Lanka.…”
Section: Primary Healthcare Teams and Community Leaders Of Rural Dry mentioning
confidence: 99%
“…Some authors have suggested Cd and other heavy metals to be factor causing such chronic kidney disease [33,48,71]. However, the existence of CKDu communities adjacent to non-CKDu communities subject to similar agrochemical exposure is consistent with other explanations [16,18,26,72]. Traditional agricultural communities have a relatively low fertizer usage.…”
Section: Introductionmentioning
confidence: 59%
“…Data are shown in figure 12 (b). Interestingly, statistical analysis indicates that 13%>0.5 ppm, 87%<0.5 ppm, 10% between 0.5 ppm and 1.0 ppm, and just one reference point had 2.86 ppm which means almost all have F − concentration below recommended maximum concentration of 1.5 ppm except just one [41,42].…”
Section: Kinetic Studiesmentioning
confidence: 99%